Teacher’s Role in Enhancing Students’ Environmental Literacy: A Systematic Literature Review 2019-2024 - Larasaty, Dwi; Rohmat, Dede; Somantri, Lili; Fitriana, Almala Nur (Jurnal Pendidikan MIPA, 2024)
Environmental issues are often heard, but there are many people who do not have awareness of these issues. Environmental ethics in everyday life are sometimes overlooked. People still need to understand how environmental bad habits will have a negative impact in the future. To have environmental awareness, environmental literacy is required. Environmental literacy can be obtained through formal and non-formal education. To improve students' environmental literacy through formal education, teachers have an important role in improving students' environmental literacy. This research aims to explore the role of teachers in improving students' environmental literacy through various effective learning methods to improve students' environmental literacy. The method used in this research is a systematic literature review with a data synthesis process using qualitative data analysis through thematic analysis. Using the PRISMA method, data selection obtained 27 articles from 678 articles on the Google Scholar and Scopus page. The results showed that teachers in various subject areas and levels can adjust the curriculum by integrating environmental literacy into learning. Effective environmental education can bridge textual learning with real-world applications. Learning outside school and interacting with the surrounding community can also improve students' environmental literacy.         Keywords: environmental literacy, teacher, students, teaching methods.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1133-1150